Prospective Elementary Teachers’ Experiences in Implementing GeoGebra-based Mathematics Activities on Area of Rectangles (Master of Elementary Education, University of Riau, 2023)
This study aims to analyze the implementation of GeoGebra-based mathematics learning as software that can assist elementary school students in understanding the concept of the rectangle area. This research was conducted by giving a GeoGebra-based activity project to a group of prospective primary school teachers from the primary school teacher education study program from a public university in the province of Riau, Indonesia. They are involved in designing and asking students' responses to the implementation of GeoGebra-based mathematics learning on finding the rectangle area. The findings revealed that students have positive views and experiences in utilizing the use of this GeoGebra software in learning mathematics. However, some students have challenges operating the GeoGebra applet due to a lack of experience in using electronic devices. As for the operation, students should use this software more often so that they are more accustomed to knowing the features available in the GeoGebra software